The spinal nerves forming the brachial plexus in mole-rats (Spalax leucodon) - Aydin, A.; Karan, M. (Czech Academy Agricultural Sciences, 2012)
In this study, the brachial plexus in the mole-rat was investigated. Six adult mole-rats were used and the brachial plexus of each was dissected. It was found that the brachial plexus in the mole-rat was formed by the rami ventralis of C5. A single root was formed from a major part of the ramus ventralis of C5 and through the joining of the whole of the ramus ventralis of C6, C7, C8 and T1. Thus, in mole-rats, the spinal nerves forming the brachial plexus and the joining of these spinal nerves to each other differ from other rodents and mammals.
Keywords: spinal nerves; rami ventralis; brachial plexus; the mole-rats (Spalax leucodon)